Kolaborasi Mahasiswa dalam Model Pembelajaran Kooperatif Tipe STAD (Student Achievement Divison) - Umar, Ali; B, Firmansyah (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
The purpose of this research is to describe the collaboration among students during the group work stage in the STAD(Student achievement Divison) cooperative learning model. The research method used descriptive qualitative. The research subjects are four students grouped based on their initial abilities. One student with high initial ability (Mt), two students with moderate initial ability (Ms), and one student with low initial ability (Mr). The research instruments used observation, interviews, and documentation. Data analysis follows the Miles & Huberman (1994) model, which consists of three stages: data reduction, data presentation, and drawing conclusions. The research findings reveal that Mt indirectly took over the discussion leadership without needing approval from other members, assumed more responsibility and a larger portion of tasks compared to other members, demonstrated dominance in presenting ideas, effectively communicated with group members, and explains ideas to other group members. On the other hand, Ms showed willingness to participate, effectively presented ideas but required approval, especially from Mt, and is more democratic and flexible in completing tasks. Meanwhile, Mr displayed reluctance to participate, passivity, hesitation in presenting ideas, and a willingness to accept other members' ideas without critiquing them beforehand.